Comparison of morphological changes of muscle fibers in response to dynamic electrical muscle contraction and dynamic hydraulic stimulation in a rat hindlimb disuse model - Hu, M; Lam, H; Yeh, R; Teeratananon, M; Qin, Y-X (Physiological research, 2017)
This study attempted to compare the muscle fiber morphological responses to dynamic electrical muscle stimulation (DEMS) and dynamic hydraulic stimulation (DHS) in rats under hindlimb suspension (HLS). DEMS at 1 Hz, 50 Hz and 100 Hz for 10 min/day, 5 days/week were introduced to the animals' right quadriceps. Static and 2 Hz DHS were introduced to the right tibiae of other animal groups on a "10 min on - 5 min off - 10 min on" loading regime for 5 days/week. In the end of the 4-week experiments, histological changes in the corresponding soleus, gastrocnemius and quadriceps of the stimulated sites were examined. Compared to age-matched, HLS led to muscle atrophy and strongly reduced muscle wet weights and averaged cross-sectional fiber areas. Among the tested DEMS frequencies, the averaged cross-sectional quadriceps fiber area in the 50 Hz group was 29 % larger than the 100 Hz group. In contrast, difference in the muscle fiber response to the static and 2 Hz DHS was not observed in either soleus or gastrocnemius. Muscle fiber morphological responses to the active DEMS was in a load frequency dependent manner under disuse condition. Relatively passive compressions, either via static or 2Hz DHS, were unable to induce any difference in the muscle fiber responses under functional disuse.
Keywords: Stress, Mechanical; orgánové kultury - kultivační techniky; zadní končetina - imobilizace; potkani Sprague-Dawley; Rats, Sprague-Dawley; náhodné rozdělení; zvířata; Rats; svalová kontrakce; Muscle Contraction; Organ Culture Techniques; mechanický stres; Random Allocation; Hindlimb Suspension; krysa rodu Rattus; ženské pohlaví; Muscle Fibers, Skeletal; Animals; elektrická stimulace; kosterní svalová vlákna; Electric Stimulation; Female